1998
DOI: 10.1111/j.1469-7793.1998.691bp.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP and glutamate are released from separate neurones in the rat medial habenula nucleus: frequency dependence and adenosine‐mediated inhibition of release

Abstract: ATP and glutamatergic synaptic currents were compared in slices of rat medial habenula nucleus using whole‐cell patch‐clamp techniques. In most cells low voltage stimulation resulted in glutamatergic responses and not purinergic responses. In five cells where ATP currents could be stimulated with low voltages, wash out of glutamate antagonists did not reveal evoked glutamate currents. Spontaneous glutamate currents confirmed washout of antagonist. Modulation of release probability of glutamate and ATP, assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 40 publications
2
39
1
Order By: Relevance
“…This had already been proposed in other reports (e.g. Barraco et al, 1995Barraco et al, , 1996Li and Henry, 1998;Okada et al, 2001;Phillis, 1998;Robertson and Edwards, 1998). However, the pharmacological and biochemical data presented in these studies do not allow distinguishing between typical striatal-like adenosine A 2A receptors and atypical receptors and/or binding sites recognized by adenosine A 2A receptor agonists.…”
Section: Discussioncontrasting
confidence: 44%
“…This had already been proposed in other reports (e.g. Barraco et al, 1995Barraco et al, , 1996Li and Henry, 1998;Okada et al, 2001;Phillis, 1998;Robertson and Edwards, 1998). However, the pharmacological and biochemical data presented in these studies do not allow distinguishing between typical striatal-like adenosine A 2A receptors and atypical receptors and/or binding sites recognized by adenosine A 2A receptor agonists.…”
Section: Discussioncontrasting
confidence: 44%
“…Here, rapid breakdown of the ATP in the synaptic cleft not only protects neurons from the excessive Ca 2+ influx initiated by receptor activation, but also results in the formation of adenosine which then curtails further ATP release [Edwards, 1996]. It has been suggested that in the medial habenula ATP and glutamate are released from separate neurons, although it may be coreleased with GABA and glycine [Robertson and Edwards, 1998;Robertson et al, 2001].…”
Section: Introductionmentioning
confidence: 98%
“…In the case of the hippocampus, the synaptic currents are potentiated by zinc (10 M), consistent with the involvement of a P2X 2 or P2X 4 subunit. There is evidence that distinct presynaptic fibers release ATP and glutamate in the medial habenula, because release of glutamate (but not ATP) is selectively inhibited by adenosine acting at presynaptic A 1 receptors (383). The amplitudes of the ATP-mediated synaptic currents recorded are uniformly small (typically 20 -50 pA) compared with EPSCs mediated by excitatory amino acids (typically Ͼ1 nA), and this certainly raises questions regarding the physiological circumstances under which such synaptic transmission comes into play.…”
Section: Endogenous Atpmentioning
confidence: 99%